Ambient Communications and Computer Systems RACCCS-2018 - Hu, Yu-Chen.; Tiwari, Shailesh; Mishra, Krishn K.; Trivedi, Munesh C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book includes high-quality, peer-reviewed papers from the International Conference on Recent Advancement in Computer, Communication and Computational Sciences (RACCCS-2018), held at Aryabhatta College of Engineering & Research Center, Ajmer, India on August 10-11, 2018, presenting the latest developments and technical solutions in computational sciences. Networking and communication are the backbone of data science, data- and knowledge engineering, which have a wide scope for implementation in engineering sciences. This book offers insights that reflect the advances in these fields from upcoming researchers and leading academicians across the globe. Covering a variety of topics, such as intelligent hardware and software design, advanced communications, intelligent computing technologies, advanced software engineering, the web and informatics, and intelligent image processing, it helps those in the computer industry and academia use the advances in next-generation communicationand computational technology to shape real-world applications. .
Reliable Data Delivery with Extended IPV4 Using Low Power Personal Area Network -- Design and Investigations of Multiband Microstrip Patch Antenna for Wireless Applications -- Nascent Approach for Noise Reduction Via EMD Thresholding -- Interactive User Interface to Advent HCI Artefact -- Phylogenetics Algorithms and Applications -- Comparative Study of Forecasting Model for Price Prediction of Rice -- Android based Blind Learning Application -- Onboard Data Acquisition System to Monitor the Vehicle -- Prediction of Employee Turnover Using Ensemble Learning -- An Empirical Study to Classify Website Using Thresholds from Data Characteristics.
Keywords: Telecommunication; Computational intelligence; Data mining; Communications Engineering, Networks; Computational Intelligence; Data Mining and Knowledge Discovery